Asuhan Keperawatan Pada Tn. S Dengan Gangguan Sistem Musculoskeletal : Post Op Fraktur 1/3 Distal Radius Ulna Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Asri Hidayatun Nasiha; Ahmad Zakiudin; Yusriani Saleh Baso (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
The musculoskeletal system is part of the body system which is responsible for movement actions and as support for the body, consisting of joints, skeletal muscles, tendons, ligaments, bursae, and other tissues that connect these structures (Kalengkongan, et al, 2021). There are several different musculoskeletal tissues and systems, the musculoskeletal system often experiences various kinds of disorders including carpal tunnel syndrome, gout, osteoarthritis, osteomyelitis, osteoporosis and fractures (Kalengkongan, et al, 2021).